The effect of immersive reminiscence therapy on anxiety and depression in people with dementia: a pilot randomized controlled trial using virtual reality headsets - Soares, Maria (2023)
This study aims to analyze the effect of reminiscence therapy using immersive virtual reality technology, in comparison with conventional reminiscence therapy, on anxiety and depressive symptoms of people with dementia. This pilot study followed a randomized controlled trial design. A convenience sample of 16 people with dementia was randomly divided in experimental and control groups. Due to health-related factors, 2 participants abandoned the study before completing the intervention. Intervention consisted of 8 biweekly individual reminiscence sessions conducted by trained researchers, in which participants in the experimental group viewed 360o videos of locations with personal relevance considering their life narratives, using virtual reality headsets to promote an immersive experience. Intervention in the control group was similar, except the videos were displayed in a computer monitor. The assessment was carried out before and after the intervention, using the Geriatric Depression Scale (15 items) and the Generalized Anxiety Disorder scale (7 items). Intervention and control groups were compared regarding sociodemographic variables and level of dementia progression at baseline. No statistically significant differences were found. Regarding the comparison of anxiety and depressive symptoms pre- and post-intervention, a slight decrease was observed in both groups, although statistical significance was not reached (p>0.05). The results of the present study do not illustrate an added value regarding the use of immersive stimuli with virtual reality technology, in reminiscence therapy programs with people with dementia. Further research is warranted to better ascertain the cost effectiveness of using these technologies in the nonpharmacological treatment of people with dementia.